2019
DOI: 10.31316/akmenika.v16i1.166
|View full text |Cite
|
Sign up to set email alerts
|

Faktor yang Mempengaruhi Tingkat Kepercayaan Penggunaan FinTech pada UMKM Dengan Menggunakan Technology Acceptance Model (TAM)

Abstract: In recent years there have been alternative technology-based capital sources called FinTech, some MSMEs have begun using FinTech as an alternative source of capital, but several other MSMEs have chosen not to use FinTech because of risks such as data confidentiality, hacker attacks and fraud. This study aims to analyze the influential factors for MSMEs in utilizing technology-based FinTech as an alternative source of capital by using the technology acceptance model (TAM) by Davis by using random purposive samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
23

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 0 publications
2
22
0
23
Order By: Relevance
“…In addition, the attitude of the public who are curious about the technology of lambaga sharia financial services at this time which is a trend in making transactions makes customers interested in using the fintech services of the Islamic financial institutions. The results of this study support other research by Liébana-Cabanillas, Sánchez-Fernández, & Muñoz-Leiva, (2014), Suyanto & Kurniawan (2019, Kurniawan (2013), andLorenzo et al (2011) that attitude will influence people's intention according to their beliefs.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, the attitude of the public who are curious about the technology of lambaga sharia financial services at this time which is a trend in making transactions makes customers interested in using the fintech services of the Islamic financial institutions. The results of this study support other research by Liébana-Cabanillas, Sánchez-Fernández, & Muñoz-Leiva, (2014), Suyanto & Kurniawan (2019, Kurniawan (2013), andLorenzo et al (2011) that attitude will influence people's intention according to their beliefs.…”
Section: Resultssupporting
confidence: 91%
“…However, different theoretical models (TAM, TRA, and TPB) have found that attitude is an important prerequisite in the intention to develop a particular behavior (Ajzen, 1980). A study revealed that the attitude of Fintech software users had a positive effect on the interest in using the software (Suyanto & Kurniawan, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…(Mahardika, 2019) menemukan persepsi kemudahan penggunaan tidak berpengaruh terhadap niat untuk menggunakan software akuntansi. Hasil penelitian tersebut didukung oleh beberapa peneliti lain (Fathinah & Baridwan, 2013), (I. C. Chang et al, 2005), (Sriwidharmanely & Syafrudin, 2012), (Suyanto & Kurniawan, 2019), (Pertiwi & Sharif, 2019), dan (Sari & Hermanto, 2016).…”
Section: Pendahuluanunclassified
“…Penelitian yang dilakukan oleh (Hermanto & Patmawati, 2017) terkait dengan penggunaan perangkat lunak akuntansi menemukan bahwa, persepsi kegunaan berpengaruh positif terhadap sikap. Hasil penelitian ini didukung oleh penelitian (Lu et al, 2010), (I. C. Chang et al, 2005), (Suyanto & Kurniawan, 2019), (Sari & Hermanto, 2016), (Pertiwi & Sharif, 2019), dan (Firdaus, 2013). H1 : Persepsi kegunaan berpengaruh positif terhadap sikap mahasiswa akuntansi untuk menggunakan MYOB Accounting.…”
Section: Hipotesis Penelitian Persepsi Kegunaan Berpengaruh Positif Terhadap Sikap Mahasiswa Akuntansi Untuk Menggunakan Myob Accountingunclassified
“…Model TAM oleh Davis, Bagozzi & Warshaw pada tahun 1989 adalah model penerimaan pengguna dan penggunaan teknologi yang paling banyak digunakan. Ini dikembangkan oleh Fred Davis dan Richard Bagozzi (Suyanto & Kurniawan, 2019).…”
Section: Technology Acceptance Model (Tam)unclassified